Individual body mass and sex of a frugivorous bird affect the quality of seed dispersal - Campagnoli, Mariana Lopes; Batisteli, Augusto Florisvaldo [UNESP]; Pizo, Marco Aurélio [UNESP]; Christianini, Alexander Vicente (My University, 2024)
Frugivorous animals play crucial roles dispersing seeds away from parental plants and influencing plant recruitment. Most studies focus on comparisons of seed dispersal services provided by distinct species of animals, but neglect how within-species variation may affect dispersal. Individual traits, such as body mass and sex, are related to metabolic rates, gut load capacity, and transit times that potentially influence dispersal quantity and quality. Here, we aim at answering if individual traits (body mass and sex) of Pale-breasted Thrushes (Turdus leucomelas) affect seed dispersal quality by testing the following hypotheses (a) individual traits influence seed retention time and germination, (b) seed retention time affects seed germination, and (c) seed passage through the gut enhances germination. We found that females retained seeds in the gut for longer periods than males. Gut passed and manually depulped seeds had similar germination success. However, heavier birds, irrespective of sex, had longer seed retention times and promoted higher germination. Our results indicate that intraspecific differences in morphological traits of frugivores are a source of variation in dispersal outputs and may help to explain complex patterns of seed dispersal. We highlight the importance of considering the quality of seed dispersal at an individual-level, as well as at a species-level, and reinforce that some individuals may contribute more to seed germination, and potentially recruitment, than others. Finally, a decrease in body masses of tropical birds in response to global warming may cascade to a decrease in seed dispersal quality. Abstract in Portuguese is available with online material.
Keywords: global warming; gut passage time; intraspecific variation; seed dispersal effectiveness; seed germination; Turdus leucomelas